LIMBA FĂRĂ LOCUIRE. EMIL CIORAN ȘI EUGÈNE IONESCO: DOUĂ CAZURI DE EXIL LINGVISTIC (Analele Universității București. Limba și literatură română, 2024)
This study aims to investigate the exile of Eugène Ionesco and Emil Cioran as a function of the linguistic modifications that occurred in their writing when they abandoned their homeland and their mother tongue, revolutionizing the ethical and aesthetic paradigms of the universal literary landscape. Dealing with their own history and making the repressed past re-emerge have allowed these authors to interrogate the present in the new language acquired starting from the Romanian-speaking literary space. This has led to various phenomena: transformations in the field of creation, starting from the break with the Romanian language, a subjective re-articulation in the field of the foreign language, starting from the triple psychoanalytic arrangement of the imaginary, the symbolic and the real, and the invention of new individualities and styles of thinking.
Keywords: Emil Cioran; Eugène Ionesco; exile; history; Romanian literature